Trends in traffic deaths before and after the passing of the non-alcohol law in Croatia in 2004 - Eduard Missoni; Missoni, E. (Актуальні проблеми транспортної медицини, 2012)
The aim of the research was to gather data as the basis to formulate theory and researchbased recommendations to policy makers with the intention of decreasing the number of alcoholrelated accidents and victims on the Croatian roads. In order to achieve that, data about the injured traffic participants and the share of participants under the influence of alcohol in the Republic of Croatia, have been collected and analysed through a fouryear period, before and after the passing of the New Road Traffic Safety Act on 20 August 2004. Цель исследования заключалась в сборе данных для разработки теоретических научно обоснованных рекомендаций для директивных органов с целью уменьшения числа связанных с алкоголем аварий и жертв на дорогах Хорватии. Для этого были собраны данные о пострадавших от дорожно-транспортных проишествий (ДТП) в Республике Хорватия участников дорожного движения и доли участников, находящихся под воздействием алкоголя. Данные проанализированы за четыре года до и после принятия новых Правил дорожного движения дорожного движения от 20 августа 2004 года. Мета дослідження полягала в зборі даних для розробки теоретичних науко
во обгрунтованих рекомендацій для ди рективних органів з метою зменшення числа пов’язаних з алкоголем аварій і жертв на дорогах Хорватії. Для цього були зібрані дані про постраждалих від дорож ньо транспортних пригод (ДТП) в Рес публіці Хорватія учасників дорожнього руху та частки учасників, що знаходяться під впливом алкоголю. Дані проаналізо вані за чотири роки до і після прийняття нових Правил дорожнього руху дорожнього руху від 20 серпня 2004 року.